AN ANALYSIS OF POLITICAL METAPHORS IN THE JAKARTA POST NEWSPAPER - Rahmah, Tiara Auliya; Dahnilsya, Dahnilsya; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research examines the use of metaphors in politics articles fromThe Jakarta Post newspaper. The objective is to identify the types of metaphors andtheir conceptual meanings. The study employs a descriptive qualitative methodology.The data sources are political articles from The Jakarta Post's online edition,specifically those related to politics. George Lakoff and Mark Johnson's theory is usedto analyze the types of metaphors, while Zoltan Kövecses' theory is used to interpret themeanings of these metaphors. The research findings include 53 instances of metaphors:21 structural metaphors, 10 orientational metaphors, and 22 ontological metaphors.The conceptual meaning of these metaphors involves interpreting them using sourceand target domains, with ontological metaphors being the most prevalent.Key Words: Metaphor, Politics Articles, The Jakarta Post